Los cubanos en Puerto Rico economía étnica e identidad cultural - Cobas, José A.; Duany, Jorge 1957- (Ed. de la Univ. de Puerto Rico, 1995)
"In-depth qualitative study of post-1959 Cuban immigration to Puerto Rico interprets Cubans as forming a middleman minority on the island. Includes chapters on the middleman minority thesis, a history of migration, the emergence of a Cuban ethnic economy, and the social organization of the community. Also available in English (Gainesville: Univ. Press of Florida, 1997)"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/